DYNAMICS OF BLOOD PRESSURE IN PERACUTE PHASE OF BRAIN STROKE - Смотрицька, Т. В.; Московко, С. П. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Almost 80% of cases of acute stroke in peracute and acute phases are accompanied by blood pressure increase, that may further сause hemorragic transformation of ischemic stroke or enhance the risk of complications, and impact the stroke consequences. According to the received data, the short-term dynamics of blood pressure has insignificant predictive value concerning the supposition about the nature of process: hemorragic or ischemic stroke, though the calculations of variability coefficient of systolic and diastolic pressure can provide valuable clinical information. Especially important is that application of thrombolysis at the ischemic stroke decreases the variability of indexes and is accompanied by preservation of the bigger part of an impaired brain.